STRATEGI PERBANKAN DALAM MENGHADAPI PERSAINGAN FINTECH: ANALISIS SWOT PADA BANK NEGARA INDONESIA CABANG MAKASSAR - Azhaq, Muhammad Hud; Alwi, Alimin; Najamuddin, Najamuddin (Media Mahardhika, 2025)
This study aims to analyze the strategy of Bank Negara Indonesia (BNI) Makassar Branch in facing competition from financial technology (fintech) companies in the digital era. The rapid development of fintech has changed the pattern of financial services, offering easy access, transaction efficiency, and more innovative technology-based services. This condition is a challenge for conventional banking, including BNI, to maintain its existence and competitiveness amidst digital disruption. The research method used is a qualitative approach with descriptive analysis. In this study, the SWOT analysis tool was used to identify the strengths, weaknesses, opportunities, and threats faced by BNI Makassar Branch. The results of the study show that BNI has strengths in the form of a wide branch network and high customer trust, but still faces weaknesses in terms of technology adaptation. Opportunities that can be utilized include the increasing need for digital financial services and the growth of the digital economy in Indonesia. Meanwhile, the threats faced come from aggressive fintech competition and changes in customer preferences. Therefore, an adaptive strategy based on digital technology, development of service products based on modern customer needs, and strengthening of data security systems are needed.